2018
DOI: 10.1002/smll.201803158
|View full text |Cite
|
Sign up to set email alerts
|

A Colloidal‐Quantum‐Dot Infrared Photodiode with High Photoconductive Gain

Abstract: on solution-processed semiconductors. Compared to them, our device shows significant merits on R and EQE that may enable more applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…Due to the high work function of glassy‐graphene, the Dirac point of graphene has been shifted down to the conduction band, resulting in an Ohmic contact, in extreme difference from the conventional Schottky barrier contact of exfoliated graphene‐transition metal dichalcogenides (TMDs), which led to a high detectivity of ~1.8 × 10 10 Jones and regular responsivity of ~12.3 mA W −1 . Besides, surface or interface engineering can also improve the device performance . Du et al explored emerging heterostructures containing graphene and its fluorine‐functionalized derivative, which played an important role in broadband‐ and IR‐sensitive photodetectors.…”
Section: Two‐dimensional Heterostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high work function of glassy‐graphene, the Dirac point of graphene has been shifted down to the conduction band, resulting in an Ohmic contact, in extreme difference from the conventional Schottky barrier contact of exfoliated graphene‐transition metal dichalcogenides (TMDs), which led to a high detectivity of ~1.8 × 10 10 Jones and regular responsivity of ~12.3 mA W −1 . Besides, surface or interface engineering can also improve the device performance . Du et al explored emerging heterostructures containing graphene and its fluorine‐functionalized derivative, which played an important role in broadband‐ and IR‐sensitive photodetectors.…”
Section: Two‐dimensional Heterostructuresmentioning
confidence: 99%
“…Besides, surface or interface engineering can also improve the device performance. 83 Du et al 52 explored emerging heterostructures containing graphene and its fluorine-functionalized derivative, which played an important role in broadband-and IRsensitive photodetectors. Fluorine-functionalized derivatives on the surface via plasma etching engineering were introduced into the system.…”
Section: Device Structures and Physical Mechanism For Photodetectionmentioning
confidence: 99%
“…They demonstrated a fast response speed with electron drift by built‐in potential derived from the difference in work functions, recording 300 ns drift transit time which had been the fastest to date . In addition to manipulating the energy level alignment between the interfaces, chemical treatments such as QD surface ligand control had been proposed as one of means to improve the response speed of QD photodiodes . In the aspect of device physics, QD's surface ligands form an insulating shell that retards charge transport between nanoparticle film and the surrounding device layers .…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of device physics, QD's surface ligands form an insulating shell that retards charge transport between nanoparticle film and the surrounding device layers . Other experimental studies on charge transport in inorganic nanocrystal films have revealed that the charge carrier mobility increases exponentially with the decrease of ligand length . In this point of view, many studies attempted to enhance inter‐QD coupling by using shorter ligand molecules, and improve electrical properties of QD films …”
Section: Introductionmentioning
confidence: 99%
“…However, all curves cross at nearly the same point, indicating that the zero responsivity point is independent of the incident intensity. It was reported in other studies on other photodetectors with a single photogate that the relation between the photocurrent I ph and incident intensity P can be expressed as follows IphPα where α is a fitting parameter related to the gate voltage biases. In our proposed MoS 2 /HfO 2 /SOI device, two photogates are presented in the top MoS 2 film and Si substrate; thus, this equation can be rewritten as follows IphPαPβ where I ph is the net photocurrent induced by dual‐photogating effects.…”
Section: Resultsmentioning
confidence: 99%